Does Electricity Drive the Development of Manufacturing Sector in Malaysia? - Husaini, Dzul Hadzwan; Lean, Hooi Hooi (Frontiers in Energy Research, 2015)
This paper investigates the relationship between electricity consumption, output, and price in the manufacturing sector in Malaysia. We find that electricity consumption, output, and price are cointegrated in the long run. In addition, it has been found that the relationship between electricity consumption and output is positive. In the long run, we find a unidirectional causality from manufacturing output to electricity consumption. This result indicates that the development of manufacturing sector stimulates greater demand for electricity. Government needs to make sure that the planning of electricity supply in the future is in line with the economic development planning to avoid shortage in electricity supply. In the short run, a unidirectional relationship runs from electricity consumption to output is found. A decrease of energy usage in production might reduce the output growth in short run. Hence, we suggest improving the efficiency of electricity usage and some cost-effective sources of energy.